PREPARATION AND CHARACTERIZATION OF POROUS ALUMINA-TITANIA AEROGEL VIA CO2 SUPERCRITICAL EXTRACTION - Silvester Tursiloadi; Hiroaki Imai; Hiroshi Hirashima (Indonesian Journal of Chemistry, 2004)
Porous aerogel of titania-alumina were prepared by hydrolysis of metal alkoxides and supercritical extraction of the solvent.  Monolithic wet-gel of 0.2TiO2-0.8Al2O3, prepared by hydrolysis of metal alkoxides in alcoholic solutions, and the solvent in wet gel was supercritically extracted in CO2 at 60oC and 24Mpa for 2h. Thermal evolutions of the microstructure of the gel were evaluated by differential thermal analysis (TG-DTA), N2 adsorption, scanning electron microscopy and X-ray diffractometer. After calcination at 500oC, the specific surface area of the gel was more than 400m2g-1. The average pore radius of aerogel, about 8nm, was about 50% of that for alumina aerogel, but about 4 times larger than that of the xerogel.  The specific surface area of the aerogel was more than 200m2g-1 after calcination at 800oC. The pore size and pore volume of aerogel hardly decreased after calcinations at 800oC, although those values of the xerogel remarkably decreased after calcination up to 800oC. The thermal stability of the microstructure of porous titania-alumina is improved by supercritical extraction.